Neural and hormonal control of food hoarding - Bartness, Timothy J. (American Physiological Society, 2011)
Many animals hoard food, including humans, but despite its pervasiveness, little is known about the physiological mechanisms underlying this appetitive behavior. We summarize studies of food hoarding in humans and rodents with an emphasis on mechanistic laboratory studies of species where this behavior importantly impacts their energy balance (hamsters), but include laboratory rat studies although their wild counterparts do not hoard food. The photoperiod and cold can affect food hoarding, but food availability is the most significant environmental factor affecting food hoarding. Food-deprived/restricted hamsters and humans exhibit large increases in food hoarding compared with their fed counterparts, both doing so without overeating. Some of the peripheral and central peptides involved in food intake also affect food hoarding, although many have not been tested. Ad libitum-fed hamsters given systemic injections of ghrelin, the peripheral orexigenic hormone that increases with fasting, mimics food deprivation-induced increases in food hoarding. Neuropeptide Y or agouti-related protein, brain peptides stimulated by ghrelin, given centrally to ad libitum-fed hamsters, duplicates the early and prolonged postfood deprivation increases in food hoarding, whereas central melanocortin receptor agonism tends to inhibit food deprivation and ghrelin stimulation of hoarding. Central or peripheral leptin injection or peripheral cholecystokinin-33, known satiety peptides, inhibit food hoarding. Food hoarding markedly increases with pregnancy and lactation. Because fasted and/or obese humans hoard more food in general, and more high-density/high-fat foods specifically, than nonfasted and/or nonobese humans, understanding the mechanisms underlying food hoarding could provide another target for behavioral/pharmacological approaches to curb obesity.